Fall Prevention: Lifestyle Factors and Fall Risk - Linda B. Bobroff; Jennifer Hillan (EDIS)
Many things can cause you to fall. The good news is that you can make some easy changes to decrease your risk of falling. This 2-page fact sheet was written by Linda B. Bobroff and Jennifer Hillan and published by the UF Department of Family Youth and Community Sciences, October 2013.